2013
DOI: 10.1021/pr300651m
|View full text |Cite
|
Sign up to set email alerts
|

PTRF/Cavin-1 is Essential for Multidrug Resistance in Cancer Cells

Abstract: Since detergent-resistant lipid rafts play important roles in multidrug resistance (MDR), their comprehensive proteomics could provide new insights to understand the underlying molecular mechanism of MDR in cancer cells. In the present work, lipid rafts were isolated from MCF-7 and adriamycin-resistant MCF-7/ADR cells and their proteomes were analyzed by label-free quantitative proteomics. Polymerase I and transcript release factor (PTRF)/cavin-1 was measured to be upregulated along with multidrug-resistant P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…For example, Cavin-1 was reported to decrease the malignant behavior of prostate PC3 cancer cells through different mechanisms, [89][90][91][92][93] although being essential for the tumor-promoting effect of Cav-1 in pancreatic cancer 94 and for multidrug resistance in breast cancer lines. 95 By analogy, even the role of Cav-1 in cancer appears to be ambiguous, because Cav-1 may behave as either a tumor suppressor or oncopromoter depending on the type of tumor. [96][97][98][99][100][101] Our data argue for an important role of Cavin-1 as essential partner of Cav-1 in RMS progression, as we clearly observed that loss of either Cavin-1 or Cav-1 was sufficient to impair cell proliferation, migration and anchorage-independent cell growth, a characteristic predictive of cell transformation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cavin-1 was reported to decrease the malignant behavior of prostate PC3 cancer cells through different mechanisms, [89][90][91][92][93] although being essential for the tumor-promoting effect of Cav-1 in pancreatic cancer 94 and for multidrug resistance in breast cancer lines. 95 By analogy, even the role of Cav-1 in cancer appears to be ambiguous, because Cav-1 may behave as either a tumor suppressor or oncopromoter depending on the type of tumor. [96][97][98][99][100][101] Our data argue for an important role of Cavin-1 as essential partner of Cav-1 in RMS progression, as we clearly observed that loss of either Cavin-1 or Cav-1 was sufficient to impair cell proliferation, migration and anchorage-independent cell growth, a characteristic predictive of cell transformation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistance cancer cells have unique plasma membrane lipid composition and organization, specifically increased sphingomyelin and rigidity (213, 224). Increased rigidity is associated with increased lipid rafts, which typically facilitate efficient cellular signaling.…”
Section: Additional Mechanisms By Which Nutritional Bioactives Exert mentioning
confidence: 99%
“…[131] Cavin1 play also a role in the MDR in breast cancer. [132] Indeed, Cavin1 is necessary for MDR in cancer cells via the fortification of lipid rafts. Since Cavin1 and Cav1 are co-transcriptionally regulated, a loss of Cavin1 will be associated with a loss of Cav1 as well.…”
Section: Caveolae New Partners and Cancermentioning
confidence: 99%